A double-layered Ge/carbon cloth integrated anode for high performance lithium ion batteries. Issue 68 (4th July 2016) - Zhang, Xiaohong; Chen, Shimou; Yu, Jia; Fang, Daliang; Zhang, Suojiang
Abstract : A double-layered Ge coated carbon cloth composite as integrated electrode shows promising application in flexible lithium ion batteries. Abstract : A double-layered Ge coated carbon cloth composite was synthesized by electrodepositing Ge from an ionic liquid using carbon cloth as substrate. As an integrated electrode, the composite exhibits a high initial charge capacity of 1169 mA h g −1 and retains 989 mA h g −1 after 100 cycles at 300 mA g −1 .